Gestational Diabetes Mellitus (GDM): Current concept and a short Review (Bangladesh Journal of Pathology, 2009)
Gestational Diabetes Mellitus (GDM) is a very common and important disease occurring during pregnancy and has detrimental effect on both the mother and the baby. The mother is at increased risk of developing obstetric complications like prolonged labour, prone to develop type 2 diabetes in future and the baby is born with overweight, cause of childhood obesity and later life development of type 2 diabetes. A short review and current concept of GDM is discussed. Key words: GDM, Type 2 diabetes, Obesity, Macrosomia, Complications   doi: 10.3329/bjpath.v24i1.2877 Bangladesh J Pathol 24 (1) : 16-20